Ethnopedagogy In The Bakayab Hai Tradition - Susanti, Pipit Aprilia; Samad , Sartika (Journal of Education Research, 2024)
Bakayab Customs Hi terms and symbols that need to be understood, each symbol in the series of customary implementations and the equipment used during the event is full of meaning. Unfortunately, the Bakayab Hai custom is only known by certain circles, for the younger generation this custom is only a ritual passed down from generation to generation without knowing its meaning. This research aims to describe the meaning of the symbols in each series of the Bakayab Hai traditional process as a whole which is related to learning based on traditional culture or ethnopedagogy. This research uses a qualitative approach because in this research data will be interpreted and presented in descriptive form or explanations in the form of words. The results of the research show that each series of processes in the Bakayab Hai tradition is related to culture-based learning or ethnopedagogy.